2013
DOI: 10.1007/978-1-4614-6130-2_27
|View full text |Cite
|
Sign up to set email alerts
|

Protection by Taurine and Thiotaurine Against Biochemical and Cellular Alterations Induced by Diabetes in a Rat Model

Abstract: In this study, the actions of taurine (TAU), a sulfonate, and thiotaurine (TTAU), a thiosulfonate, on diabetes-mediated biochemical alterations in red blood cells (RBCs) and plasma and on the RBC membrane, morphology and spectrin distribution were examined in rats. Diabetes was induced in male Sprague-Dawley rats with streptozotocin (60 mg/kg i.p.) and allowed to progress for 14 days. From days to 56, the rats received a daily, 2.4 mmol/kg, oral dose of TAU or TTAU, 2 mL oral dose of physiological saline or 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Taurine is a conditionally essential amino acid that contains a sulfonic acid group and has several physiological roles ( 37 , 38 ). Increasing evidence has shown that taurine exerts strong protective effects due to its antioxidant characteristics ( 17 , 39 , 40 ). In the present study taurine levels in the liver were increased to investigate whether this prevented iron overload-induced hepatic damage, despite the fact that taurine has no effect on iron deposition.…”
Section: Discussionmentioning
confidence: 99%
“…Taurine is a conditionally essential amino acid that contains a sulfonic acid group and has several physiological roles ( 37 , 38 ). Increasing evidence has shown that taurine exerts strong protective effects due to its antioxidant characteristics ( 17 , 39 , 40 ). In the present study taurine levels in the liver were increased to investigate whether this prevented iron overload-induced hepatic damage, despite the fact that taurine has no effect on iron deposition.…”
Section: Discussionmentioning
confidence: 99%
“…Phospholipids levels increased in tissues of streptozotocin diabetic rats [18][19][20][21] . Administration of whole plant ethanol extract of E. alsinoides and glibenclamide decreased the levels of phospholipids in both liver and kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Taurine (2-aminoethanesulfonic acid) is an organic acid widely found in various animal tissues. It has many fundamental biological functions including bile acids, antioxidation, osmoregulation, membrane stabilization, and modulation of calcium signaling [18]. In addition, betaine (trimethylglycine) is a dietary component, and farm animal studies showed that inclusion of betaine in feed produced leaner meat with a lower fat content [19].…”
Section: Measurements Of Representative Components In Oyster Shellmentioning
confidence: 99%
“…In addition, betaine (trimethylglycine) is a dietary component, and farm animal studies showed that inclusion of betaine in feed produced leaner meat with a lower fat content [19]. Both of these components are known to have a lipid-lowering effect and improve diabetic conditions [18].…”
Section: Measurements Of Representative Components In Oyster Shellmentioning
confidence: 99%